Mit o materinstvu - Štular, Suzana (Časopis za kritiko znanosti, 1999)
The article presents motherhood and sexual identity as part of contemporary mythology and not as the achievements of objective science. A critical insight into scientific production and, above all, the presumption about the social construct of reality point to the hidden sources of meaning which do not function at or originate from the level of the mind. Science is therefore defined by mythical elements as specific forms of social awareness that are inconstant interaction with the past and future. Through guilt as one of important elements of the "good" mother image both in Christian and scientific contexts, the article reveals that the general beliefs about motherhood and femininity are part of western society's mythology. The understanding of the "good" mother image as part of mythology is placed within the context of gentile relations, which facilitates a different reading of the new draft law on maternity leave within the context of sexual identity constructs.
Keywords: miti; mythology; mitologija; materinstvo; spolna identiteta